The Relationship of Sanitation Hygiene of Grilled Sausage at Car Free Day (CFD) Malang to Bacteria Colonies Number - Hariyati, Nabila; Budiyanto, Moch. Agus Krisno; Husamah, H. (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2018)
The number of bacteria in the grilled sausage is affected by sanitation hygiene. Aspects of hygiene sanitation include food handlers, equipment, presentation, means of peddlers, and merchant centers. If these five aspects do not meet the standards then it can trigger the occurrence of food contamination by microorganisms. This study aims to determine whether there is a hygiene relationship sanitation traders on the number of bacterial colonies roasted sausages in the car free day (CFD) of Malang City. Data collection using observation sheet referred to Decree of Minister of Health, Number 942/MENKES/SK/VII/2003. Data in the form of hygiene sanitation score. Product moment correlation is used to analyze the presence or absence of relationship between variables. Result of research indicate that there is relation of sanitation hygiene of merchant to the number of bacteria in burning sausage in Car Free Day (CFD) Malang. Keywords: hygiene sanitation, grilled sausage, the number of bacteria